Detection of Antibiotic Residues in Chicken Meat and Eggs from Traditional Markets at Yogyakarta City Using Bioassay Method - Dyah Ayu Widiasih; Yatri Drastini; Doddi Yudhabuntara; F. Lintang R. Daru Maya; Prisha Lini Sivalingham; Heru Susetya; Widagdo Sri Nugroho Sri Nugroho; M. Th. Khrisdiana Putri; Roza Azizah Primatika; Bambang Sumiarto (Acta VETERINARIA Indonesiana, 2019)
Studies on antibiotic residues content in food of animal origin are currently needed to support veterinary public health programs. The present study was described bioassay method for the detection of antibiotic residues in chicken meat and eggs from traditional market at Yogyakarta City. A number of twenty-four chicken meat samples and 24 egg samples were taken from 8 traditional markets in Yogyakarta city. Samples were examined at Centre for Veterinary Wates, Yogyakarta, Indonesia using bioassay method for screening detection of penicillin, aminoglycoside, macrolide and tetracycline residues. This bioassay method using some bacteria, such as Bacillus stearothermophillus, B. cereus, B. subtilis, and Kocuria rizophila. A percentage of the results showed that 8.33% (2/24) samples of chickens tested positively contained the oxytetracycline antibiotic residues. Meanwhile, as much as 75% (18/24) samples of positive eggs contain penicillin antibiotic residues, positive residues of aminoglycoside amounted to 12.5% (3/24) and the positive residues of oxytetracycline also amounted to 12.5% (3/24).